2020
DOI: 10.1002/jeq2.20056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of no‐till and a winter rye cover crop on nitrate losses from tile‐drained row‐crop agriculture in Iowa

Abstract: Artificial subsurface drainage is necessary to maintain agricultural production in the soils and climate of north‐central Iowa. However, it can result in adverse environmental impacts, because it intercepts and diverts some water and soluble NO3–N directly to streams. We investigated the impact of no‐till and a winter rye cover crop (Secale cereale L.) on seasonal and annual NO3–N concentration and loading in leachate from a corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] rotation. The eight treatments are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 57 publications
(127 reference statements)
0
32
1
Order By: Relevance
“…Similar to trends observed for surface runoff concentrations and loads, infiltration water N and P concentrations were generally lower in grass pasture compared to cover crop and wheat and postgraze concentrations were lower than pre-graze. Infiltration water NO 3 − -N and PO 4 3− -P concentrations were greater in cover crop and wheat phases, yet these concentrations were up to an order of magnitude lower than observed in leachate of previous studies (Delgado, Shaffer, & Brodahl, 1998;Waring, Lagzdins, Pederson, & Helmers, 2020;Wilson, Tyler, Logan, & Turnage, 1991), indicating a low leaching potential for ICL system vegetation types in the northern Great Plains ecoregion examined herein.…”
Section: Discussioncontrasting
confidence: 64%
“…Similar to trends observed for surface runoff concentrations and loads, infiltration water N and P concentrations were generally lower in grass pasture compared to cover crop and wheat and postgraze concentrations were lower than pre-graze. Infiltration water NO 3 − -N and PO 4 3− -P concentrations were greater in cover crop and wheat phases, yet these concentrations were up to an order of magnitude lower than observed in leachate of previous studies (Delgado, Shaffer, & Brodahl, 1998;Waring, Lagzdins, Pederson, & Helmers, 2020;Wilson, Tyler, Logan, & Turnage, 1991), indicating a low leaching potential for ICL system vegetation types in the northern Great Plains ecoregion examined herein.…”
Section: Discussioncontrasting
confidence: 64%
“…Cereal rye (Secale cereale L.) has been widely used in the upper Midwest because of its winter-hardiness and its ability to scavenge postharvest soil N compared with other species (Kaspar & Bakker, 2015). While previous studies have shown reductions in NO 3 -N concentrations in subsurface drainage provided by cereal rye (Kaspar et al, 2007(Kaspar et al, , 2012Ruffatti et al, 2019;Waring et al, 2020), many producers remain apprehensive about cover crop adoption. One of the obstacles of planting cereal rye ahead of corn is the potential reduction of early-season soil N availability due to net N immobilization, resulting in 0.1-12% yield reductions…”
Section: Introductionmentioning
confidence: 99%
“…Subsurface drainage from agricultural fields in Iowa has been identified as a major source of nitrogen and phosphorus delivered to downstream water bodies (Baker et al, 1975;Helmers et al, 2005;Waring et al, 2020). These nutrients are known to cause hypoxia in the Gulf of Mexico (Hypoxia Action Plan, 2008).…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
“…Existing subsurface drainage infrastructure is rerouted from usual outlets or nearby streams to a storage reservoir near the field. Because a large portion of Iowa's subsurface drainage usually occurs in the spring (Waring et al, 2020), it is kept in the reservoir until rainfall and stored soil water cannot meet crop water 2 demands. At this point the captured subsurface drainage water is applied to the field to alleviate drought stress in the crop (Frankenberger et al, 2017).…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
See 1 more Smart Citation